Answer:
x=2, x=1, x=-5 and x=-3.
Explanation:
Let's find the answer using the following method.
Original equation:
![30 -29x - 7x^2+5x^3 + x^4=0](https://img.qammunity.org/2020/formulas/mathematics/college/c09fcvzbamxbuuxzef4cmvjjdmzcmptlg6.png)
Notice that the constant term is 30, which can be divided by:
1, -1, 2, -2, 3, -3, 5, -5, 6, -6, 10, -10, 15, -15, 30, -30.
Trying this divisors can allowed us to find one or even two initial roots, so:
Trying first x=1, we have:
![30 -29x - 7x^2+5x^3 + x^4=0](https://img.qammunity.org/2020/formulas/mathematics/college/c09fcvzbamxbuuxzef4cmvjjdmzcmptlg6.png)
![30 -29*(1) - 7*(1)^2+5*(1)^3 + (1)^4=0](https://img.qammunity.org/2020/formulas/mathematics/college/hw2fdw4t5uy4uofp6sp12sxltaybd77mn7.png)
![30 -29 - 7+5 + 1=0](https://img.qammunity.org/2020/formulas/mathematics/college/dta3zj2bz4my2xmil4gxwnegn95w48uvea.png)
notice that x=1 is a root.
Let's try now with x=2, we have:
![30 -29x - 7x^2+5x^3 + x^4=0](https://img.qammunity.org/2020/formulas/mathematics/college/c09fcvzbamxbuuxzef4cmvjjdmzcmptlg6.png)
![30 -29*(2) - 7*(2)^2+5*(2)^3 + (2)^4=0](https://img.qammunity.org/2020/formulas/mathematics/college/nryrpyysjapwjsna9ykgx4n3jsg6r800pt.png)
![30 -58 - 28+40 + 16=0](https://img.qammunity.org/2020/formulas/mathematics/college/cnb7yhq3x8d7ghqddtxlu9qigy1d5to04v.png)
notice that x=2 is also a root.
So the original equation can be written as:
so:
Doing the math, we have:
now:
![(30 -29x - 9x^2+8x^3)-(8x)*(x^2 - 3 x + 2)=](https://img.qammunity.org/2020/formulas/mathematics/college/jzohcr9mbr3h00xrkqwohpu21osphnkd1u.png)
![(30 -29x - 9x^2+8x^3)-(8x^3 - 24 x^2 + 16x)=](https://img.qammunity.org/2020/formulas/mathematics/college/c2su46yz3gx6rr1t3tl0by19pmwoe0zwtt.png)
now:
![(30 -45x +15x^2)-(15)*(x^2 - 3 x + 2)=](https://img.qammunity.org/2020/formulas/mathematics/college/c7hsicbjcxa0fkmqlfc7f6rq8xy7ox056k.png)
![(30 -45x +15x^2)-(15x^2 - 45 x + 30)=0](https://img.qammunity.org/2020/formulas/mathematics/college/jyiurozd8r13mriee10na2013xfxr9o72b.png)
which means:
Using the equation for calculating the roots of a quadratic equation we have:
quadratic equation:
![x=(-b\±√(b^2-4ac) )/(2a)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/r0wks1tt1il7bxuwf9xudkzvhtrqrsa5it.png)
![x=(-8\±√((8)^2-(4*1*15)) )/(2*1)](https://img.qammunity.org/2020/formulas/mathematics/college/fm6nzun2dvxgoteirheogodbpkzssdtx6c.png)
![x=(-8\±√((8)^2-(4*1*15)) )/(2*1)](https://img.qammunity.org/2020/formulas/mathematics/college/fm6nzun2dvxgoteirheogodbpkzssdtx6c.png)
![x=(-8\±\2)/(2)](https://img.qammunity.org/2020/formulas/mathematics/college/1zqdy5ltmg5szfdokimbm1ttdtml7f8z12.png)
![x1=-5](https://img.qammunity.org/2020/formulas/mathematics/college/i193js04y3kh364d4d81zcn5d94fmi8vkq.png)
![x2=-3](https://img.qammunity.org/2020/formulas/mathematics/college/lmvurszfy0vbobaiaq7vsrdnpxxbtuke48.png)
So finally we have:
In conclusion the roots are: x=2, x=1, x=-5 and x=-3.